COVID‐19 and the impact on rural and black church Congregants: Results of the C‐M‐C project. Issue 5 (5th July 2021) - Williams, Lovoria B.; Fernander, Anita F.; Azam, Tofial; Gomez, Maria L.; Kang, JungHee; Moody, Cassidy L.; Bowman, Hannah; E. Schoenberg, Nancy
Abstract: The COVID‐19 pandemic has had devastating effects on Black and rural populations with a mortality rate among Blacks three times that of Whites and both rural and Black populations experiencing limited access to COVID‐19 resources. The primary purpose of this study was to explore the health, financial, and psychological impact of COVID‐19 among rural White Appalachian and Black nonrural central Kentucky church congregants. Secondarily we sought to examine the association between sociodemographics and behaviors, attitudes, and beliefs regarding COVID‐19 and intent to vaccinate. We used a cross sectional survey design developed with the constructs of the Health Belief and Theory of Planned Behavior models. The majority of the 942 respondents were ≥36 years. A total of 54% were from central Kentucky, while 47.5% were from Appalachia. Among all participants, the pandemic worsened anxiety and depression and delayed access to medical care. There were no associations between sociodemographics and practicing COVID‐19 prevention behaviors. Appalachian region was associated with financial burden and delay in medical care ( p  = 0.03). Appalachian respondents had lower perceived benefit and attitude for COVID‐19 prevention behaviors ( p  = 0.004 and <0.001, respectively). Among all respondents, the perceived risk of contracting COVID was high (54%), yet 33.2% indicated unlikeliness to receive the COVID‐19 vaccine if offered. The COVID‐19 pandemic had a differential impact on White rural and Black nonrural populations. Nurses and public health officials should assess knowledge and explore patient's attitudes regarding COVID‐19 prevention behaviors, as well as advocate for public health resources to reduce the differential impact of COVID‐19 on these at‐risk populations.